Nanoparticle activation methods in cancer treatment - White, B; Duan, C; Townley, H (MDPI, 2019)
In this review, we intend to highlight the progress which has been made in recent years around different types of smart activation nanosystems for cancer treatment. Conventional treatment methods, such as chemotherapy or radiotherapy, suffer from a lack of specific targeting and consequent off-target effects. This has led to the development of smart nanosystems which can effect specific regional and temporal activation. In this review, we will discuss the different methodologies which have been designed to permit activation at the tumour site. These can be divided into mechanisms which take advantage of the differences between healthy cells and cancer cells to trigger activation, and those which activate by a mechanism extrinsic to the cell or tumour environment.